CHARITABLE AND SOCIALLY USEFUL ACTIVITIES OF THE THIRD SECTOR IN PUBLIC ASSESSMENTS - Rogach, Olga; Frolova, Elena; Demina, Svetlana; Ryabova, Tatyana; Medvedeva, Natalia (Revista Inclusiones, 2020)
The article presents the results of a study aimed at studying the attitude of Moscow residents to charitable and socially useful activities. The key research method is a telephone survey of Muscovites aged 18 to 65 years. The sample consisted of 1,006 respondents. According to the data obtained, the highest level of activity in charitable and socially useful activities was shown by women with higher education, as well as women with minor children. The most preferred forms of charitable activity are identified: collecting money, things and products, providing information support. The results of the study showed a low level of confidence of Muscovites in the activities of NGOs, which is due to the lack or insufficiency of control over the expenditure of their financial resources. The problem of information vacuum around the work of the third sector is revealed. Respondents do not have a complete understanding of the specifics of charitable activities of NGOs and are not informed about the events held and their significance.